The Influence Of Power On Individual Cooperation Development Among Teenagers’ Students In China - Zhang, Lei (2024)
Cooperation is an important manifestation of prosociality (i.e., voluntary thoughts and actions intended to benefit somebody else). Exploring the cooperation development of teenagers can further reveal the development law of their prosociality. Adopting teenagers of different ages as research objects, this study explores the influence of a sense of power on the development of different levels of cooperation (sense of cooperative, cooperative cognition, and cooperative behavior). Research was conducted among teenagers in a middle school, a high school, and a university in Huizhou, Guangdong, China.